2016
DOI: 10.1002/per.2038
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Dimensions of Impulsivity and Prospective Memory

Abstract: Prospective memory refers to the ability to plan and execute future intentions. A burgeoning body of research indicates that a significant proportion of the variability in prospective memory performance can be accounted for by personality traits, with two recent studies revealing that the various dimensions of impulsivity measured by the Barratt Impulsivity Scale‐11 (BIS‐11) are related to prospective memory failures. The present study was conducted to examine which dimensions of impulsivity indexed by the BIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
(91 reference statements)
4
4
0
Order By: Relevance
“…For the baseline task, impulsivity, in particular sensation seeking and positive urgency, was associated with reduced performance. This agrees with previous positive findings on impulsivity and PM (Cuttler et al, 2014(Cuttler et al, , 2016 and with the theoretical perspectives in which PM would be expected to require reflective processing/executive functions/strategic processes and therefore be negatively affected by impulsivity. Impulsivity could affect PM performance at the point of performing the intended task, or by causing participants to skip past PM task instructions and failing to encode the instructed PM task into memory in the first place.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For the baseline task, impulsivity, in particular sensation seeking and positive urgency, was associated with reduced performance. This agrees with previous positive findings on impulsivity and PM (Cuttler et al, 2014(Cuttler et al, , 2016 and with the theoretical perspectives in which PM would be expected to require reflective processing/executive functions/strategic processes and therefore be negatively affected by impulsivity. Impulsivity could affect PM performance at the point of performing the intended task, or by causing participants to skip past PM task instructions and failing to encode the instructed PM task into memory in the first place.…”
Section: Discussionsupporting
confidence: 92%
“…From this perspective, it would therefore be expected that more impulsive individuals would show weaker PM performance. Relationships between PM and various facets of impulsivity have indeed previously been shown (Cuttler et al, 2014(Cuttler et al, , 2016, but Prospective memory and impulsivity 5 this was not the case in all studies or for all measures (Chang & Carlson, 2014;Uttl et al, 2018).…”
Section: Introductionmentioning
confidence: 73%
“…The available evidence partially supports this point. For example, studies using BIS-11 and PM questionnaires to explore the relationship between impulsiveness and PM performance found that individuals with lower impulsivity scores had better self-reported PM performance [14,15], which is consistent with our predicitions. However, the use of self-reported questionnaires to reflect an individual's PM ability tends to be more subjective, while the dual-task paradigm used to measure an individual's PM ability under the laboratory condition has been widely shown to be objective and effective [16,17].…”
Section: Introductionsupporting
confidence: 88%
“…Prospective Memory Questionnaire (Revised Version; Hannon et al, 1990Hannon et al, , 1995. We used a modified version of the Prospective Memory Questionnaire (PMQ; Cuttler et al, 2016) because participants had difficulties understanding the original scale (Cuttler & Taylor, 2012;Uttl & Kibreab, 2011). Participants responded to 52 items (e.g., I missed appointments I had scheduled) using a Likert scale ("1" never to "5" very often).…”
Section: Questionnairesmentioning
confidence: 99%